Administrative and legal prohibition as a means of combating corruption in the State Penitentiary Service of Ukraine - Бондарчук, О. Г. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article explores the impact of administrative and legal restrictions on the behavior of civil servantsas a means of legal regulation of state-business relations. Particular attention is paid to the prohibitions asadministrative and legal mechanism against corruption in public service.